Genetic Variation and Metabolic Basis of Kidney Cancer: New Opportunities for Targeted Therapy - M. F. Urmantsev; R. I. Tavabilov; M. R. Bakeev (Креативная хирургия и онкология, 2024)
Renal cell carcinoma (RCC) has previously been considered as a single disease. However, it is currently characterized as a heterogeneous group of tumors that differ in histological features, genetic abnormalities, and variable clinical course. In normal cells, energy is produced by the cleavage of chemical bonds in nutrients through the oxidation of fats, proteins, or carbohydrates. Mutational alterations in genes associated with RCC, including VHL, FLCN, PTEN and SDH, lead to abnormal cellular adaptation to changes in oxygen status, iron metabolism and nutrients. The present paper reviews the known genetic abnormalities observed in RCC and their impact on metabolic alterations. Understanding the genetic and metabolic mechanisms underlying RCC is crucial for the development of effective therapies. Targeting specific genetic abnormalities or metabolic pathways represents a promising approach to the RCC treatment. In addition, studies into the metabolic basis of RCC contribute to the development of new biomarkers for early diagnosis and monitoring of the disease. Moreover, investigating the role of VHL, FLCN, PTEN, and SDH genes in the development of RCC provides valuable information on the molecular mechanisms behind the disease. As a result, it may lead to the development of new treatment strategies aimed at restoring the normal function of these genes or compensating for their abnormalities. Overall, an integrated approach to the study of RCC that considers genetic, metabolic, and clinical aspects will ensure that more effective treatments are developed and prognosis for patients with this disease are improved.